2004
DOI: 10.1212/01.wnl.0000104491.66816.77
|View full text |Cite
|
Sign up to set email alerts
|

Novel SACS mutations in autosomal recessive spastic ataxia of Charlevoix-Saguenay type

Abstract: Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is an early-onset familial disease with prominent myelinated fibers in the optic fundus. ARSACS is frequent in the Charlevoix-Saguenay region of Quebec but rare elsewhere. Mutations in SACS, encoding sacsin, a protein of unknown function, are associated with ARSACS. The authors identified three new SACS mutations in two Italian patients whose phenotype closely matches that of Quebec cases, but without retinal striation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 9 publications
2
60
0
Order By: Relevance
“…Age at onset was late childhood in agreement with Baets et al 28 and higher than what was reported in Tunisian patients. 29 Both patients had absent fundal striations in accordance with previous reports of Italian patients 30,31 and Japanese sibship. 32 The family history revealed three brothers who were clinically diagnosed with Laurence Moon Biedl syndrome and died from renal failure years ago (suggesting a second segregating disease gene within the same family, although this was not genetically analyzed).…”
Section: Phenotype-genotype Correlationssupporting
confidence: 89%
“…Age at onset was late childhood in agreement with Baets et al 28 and higher than what was reported in Tunisian patients. 29 Both patients had absent fundal striations in accordance with previous reports of Italian patients 30,31 and Japanese sibship. 32 The family history revealed three brothers who were clinically diagnosed with Laurence Moon Biedl syndrome and died from renal failure years ago (suggesting a second segregating disease gene within the same family, although this was not genetically analyzed).…”
Section: Phenotype-genotype Correlationssupporting
confidence: 89%
“…The phenotype observed in persons of Tunisian heritage differs from that observed in Quebec-born individuals in the very low incidence of retinal networks of myelinated fibers and the later age of onset 11 . Grieco et al described three new SACS mutations in two of the original six Italian families and in two individuals the phenotype was similar to that reported in Quebec-born individuals with ARSACS except for the absence of retinal striations 8 . Similarly, our patients had no retinal alterations.…”
Section: Cases Descriptionsupporting
confidence: 68%
“…ARSACS diagnosis is based on clinical manifestation, neuroimaging features and confirmed by demonstration of the deletion in the sacsin gene, located on chromosome 13q1 3 . Neuropathologic findings showed pyramidal degeneration, cortical atrophy, atrophy of the superior cerebellar vermis and loss of motoneurons 8 . The causal mutations in the SACS gene in individuals from northeastern Quebec include two founder mutations, a single-base deletion at position 6594 (6594delT) and a 5254C>T nonsense mutation 9 .…”
Section: Cases Descriptionmentioning
confidence: 99%
“…SACS gene identification has enabled us to find ARSACS patients worldwide outside Quebec: Tunisia (El Euch-Fayache et al, 2003) in 2003, Italy (Criscuolo et al, 2004;Grieco et al, 2004)in 2004, Japan (Ogawa et al, 2004) in 2004, and Turkey (Richter et al, 2004) …”
Section: Non-quebecmentioning
confidence: 99%
“…In 2000, the SACS gene, which is responsible for ARSACS, was identified in Quebec patients (Engert et al, 2000). Since then, ARSACS has been reported worldwide, especially in the Mediterranean area (El Euch-Fayache et al, 2003;Criscuolo et al, 2004;Grieco et al, 2004;Richter et al, 2004) and Japan (Ogawa et al, 2004;Takiyama, 2006). More SACS gene mutations were also identified in other areas (Takiyama, 2007;Ouyang et al, 2008;Vermeer et al, 2008;Gerwig et al, 2010).…”
Section: Introductionmentioning
confidence: 99%